2012
DOI: 10.1111/j.1349-7006.2012.02210.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and chemokine modification by Toll‐like receptor polymorphisms is associated with nasopharyngeal carcinoma

Abstract: Toll-like receptors (TLR) play a pivotal role in sensing a wide range of pathogens, including bacteria, fungi and viruses. A dysregulation of TLR signaling may increase the risk of developing chronic inflammatory diseases and cancers. The aim of this study was to investigate the association of TLR2 R753Q, TLR4 D299G, and T399I polymorphisms with nasopharyngeal carcinoma (NPC) and to explore the effects of these polymorphisms on cytokine and chemokine expression in NPC biopsies. The genotypes of the three loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 36 publications
0
27
0
1
Order By: Relevance
“…It has been reported that TLRs genes are expressed on endothelial, epithelial cells and tumour cells, including head and neck cancer cells (Huang et al, 2005;Szczepanski et al, 2009;Bergmann et al, 2011;Chuang et al, 2012;Theodoropoulos et al, 2012). Dysregulation in TLRs signalling has previously been associated with a higher risk of developing different types of cancers, including prostate, cervical and nasopharyngeal carcinoma (Pandey et al, 2009;Yang et al, 2012). TLR3 gene is expressed in different malignant cells, such as breast cancer and melanoma (Chuang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that TLRs genes are expressed on endothelial, epithelial cells and tumour cells, including head and neck cancer cells (Huang et al, 2005;Szczepanski et al, 2009;Bergmann et al, 2011;Chuang et al, 2012;Theodoropoulos et al, 2012). Dysregulation in TLRs signalling has previously been associated with a higher risk of developing different types of cancers, including prostate, cervical and nasopharyngeal carcinoma (Pandey et al, 2009;Yang et al, 2012). TLR3 gene is expressed in different malignant cells, such as breast cancer and melanoma (Chuang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have shown that the T399I mutation in TLR4 enhances the expression of TNFα message, which is associated with the risk of nasopharyngeal carcinoma development 112 . This represents a potentially more direct link between the T399I mutation in TLR4 and excessive CHI3L1 expression in nasopharyngeal epithelial cells via TNFα.…”
Section: Introductionmentioning
confidence: 99%
“…Two missense (non‐synonymous) mutations have been identified in the TLR4 gene: replacement of aspartic acid with glycine at amino acid 299 (rs4986790) and replacement of threonine with isoleucine at amino acid 399 (rs4986791). Previous findings have reported that these polymorphisms affect the expression of inflammatory cytokines and chemokines and are associated with the progression of head and neck cancer . In the current study, no associations between these polymorphisms in the TLR4 gene and OLP occurrence were observed.…”
Section: Discussionmentioning
confidence: 99%